CARTOGRAFÍA DE PAISAJES: UNA HERRAMIENTA PARA EL INVENTARIO Y LA JERARQUIZACIÓN DE LOS RECURSOS TURÍSTICOS EN EL EXTREMO AUSTRAL DE LA PATAGONIA - Elizabeth Mazzoni (Boletín Geográfico)
Landscape units defined for the southeast portion of the continental Patagonia Argentina are presented, which have been defined with particular reference to their physical features, thay are the main elements of differentiation in the area. This systematization aims to inventory and prioritize tourism resources of the region and the scenic assessment of each landscape. Each unit was digitized on screen on Landsat ETM+ satellite image of the area, which has a spatial resolution appropriate to the worksheet scale 1: 250,000. In the different units there have been inventoried tourist interest resources, especially associated with non-conventional modalities: scientific, rural, bird watching, fishing, among others.